Construct Validity Test of Integrity and Suryomentaram-style Introspection in Creating Anti-Fraud - Mustika Prabaningrum Kusumawati; Ari Nur Rahman (Association of Certified Fraud Examiners Indonesia Chapter, 2023)
The high level of corruption and fraud in Indonesia is one of the crucial problems that must be resolved immediately by the Government of Indonesia. Various efforts to eradicate corruption and the creation of anti-fraud will not be optimal if the habit of applying the meaning of integrity in actions and behavior, which begins with the determination of an employee or public official, is still mixed with the desire to enrich oneself and one’s class. The identification of the problem in this study includes 3 (two) things. First, does the construct of measuring instrument of integrity and Suryomentaram-style introspection supports the efforts to prevent fraud and corruption and fulfill unidimensionality by using confirmatory factor analysis? Second, does the measuring instrument of integrity and Suryomentaram-style introspection in this study consists of items that fit in measuring integrity and Suryomentaram-style introspection using the application of the polytomous IRT model? Third, do the items in the measuring instrument of integrity and Suryomentaram-style introspection in this study contain a response bias based on gender that can be detected through differential item functioning (DIF)?. This research was conducted with the aim of obtaining measuring instrument of integrity and Suryomentaram-style introspection that supports steps to prevent fraud and corruption at the level of implementing employees to managers in Indonesian companies and/or state institutions.